Course of a new coronavirus infection in children: some aspects of monitoring and analysis of mortality - A. N. Uskov; Yu. V. Lobzin; S. V. Rychkova; I. V. Babachenko; V. V. Fedorov; L. U. Ulukhanova; L. M. Pochinyaeva (Журнал инфектологии)
The work objective was to carry out the analysis of the existing in the Russian Federation monitoring of the incidence of new coronavirus infection in children and specific features of death cases caused by COVID-19 in children. Materials and methods. The analysis of the data of operative statistics presented on the sites of the governments of the regions where the incidence among children was considered within the period from April 22, 2020 to June 26, 2020, as well as the data of the Main non-staff experts in infectious diseases in children was performed. The inpatient medical documentation and the data of pathologicoanatomic investigation of children died due to COVID-19 were analyzed. Results. Prevalence of COVID-19 in children from various regions of the Russian Federation was from 1% to 8.6% in the structure of general disease incidence. The asymptomatic and mild forms of the disease which did not require hospitalization, were noted in 55–60% of the cases. 12 death cases associated with COVID-19 were registered for June 22, 2020. The analysis of 8 presented cases showed that 6 patients out of 8 died children were of the first half of the year of life (3 girls and 5 boys). In most cases the children were admitted to the hospital at the 8–12th day of the disease in severe and extremely severe condition due to pulmonary-cardiac insufficiency, six patients had fever up to 38–39°С, four patients had signs of consciousness depression. All children were diagnosed with community-acquired bilateral pneumonia according to the data of roentgenography, ultrasound investigation or computer tomography of the chest organs that did not always coincide with the intensity of respiratory syndrome. The direct cause of death was cardiac or pulmonary-cardiac insufficiency. Conclusion. The analysis of clinical and laboratory manifestations of COVID-19 with an unfavourable outcome in children revealed some difficulties in the interpretation of its role in thanatogenesis. The significance of comorbid pathologies in the development of unfavourable outcomes is doubtless.